(untitled) (Bioagro, 2026)
Cilantro (Coriandrum sativum L.) is widely used in culinary, pharmaceutical, and cosmetic industries. Proper nutritional management is essential for the growth and quality of plants in hydroponic cultivation. This study evaluated the growth, macronutrient content, and phenolic compounds in cilantro under different concentrations of nutrient solutions. The experiment, conducted in a greenhouse, followed a randomized block design with six treatments (25% to 150% of Hoagland and Arnon ionic strength) and five replicates. Plants were harvested 60 days after sowing for analysis of height, dry mass, leaf area, macronutrients, and total phenols. Maximum growth occurred between 80% and 100% ionic strength. Nitrogen (N) and potassium (K) showed higher concentrations at 85% and 63.5%, respectively, while phosphorus (P) increased up to the maximum concentration, corresponding to 150% of the ionic strength, and calcium (Ca), magnesium (Mg), and sulfur (S) decreased at higher ionic strength. The content of phenolic compounds decreased with increasing ionic strength. It is concluded that ionic strength directly influences the growth, nutrition, and quality of cilantro, requiring a nutritional balance to maximize production and the quality of secondary metabolites.